Geometric and convolution properties of uniformly starlike functions. - Mohamed Ali, Rosihan
This research focuses on the investigation of the properties certain subclasses of analytic functions, At the beginning, it aims to study the uniformly starlikeness properties of analytic functions. Along the way, researches also have been done on determing the sufficient conditions for starlikeness, convexity and close·to-convexity of a few subclasses of analytic functions.